Police Leadership Training: Effective Policies and Methods - Abdelmottlep, Mamdooh A. (International Journal of Police Science, 2023)
Modern security institutions face important issues related to police leadership training and contemporary security challenges. The scope and context of training programs in security institutions must be evaluated to develop effective policies and methods for training security leaders. The International Police Science Association (IPSA) aims to support effective training approaches and other aspects of effective policing by supporting and sharing international scientific efforts in police science.